1995
DOI: 10.1002/jbmr.5650100411
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of swimming versus weight-bearing activity on bone mineral status of eumenorrheic athletes

Abstract: To examine the role of skeletal loading patterns on bone mineral density (BMD), we compared eumenorrheic athletes who chronically trained by opposite forms of skeletal loading, intensive weight-bearing activity (gymnastics, n = 13), and nonweightbearing activity (swimming, n = 26) and 19 nonathletic controls. BMD (g/cm2) of the lumbar spine, femoral neck, trochanter, and whole body was assessed by dual energy X-ray absorptiometry (DXA). Subregion analysis of the whole body scan permitted BMD evaluation of dive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
96
1
6

Year Published

1996
1996
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 255 publications
(108 citation statements)
references
References 45 publications
(3 reference statements)
5
96
1
6
Order By: Relevance
“…Therefore, it was suggested that an optimal combination of land and water exercises should be prescribed to patients with RA, dependent on the patients' needs and disease activity at that period of time. 57 Physical assessment and possible adverse effects of exercise…”
Section: Strengthening Exercisesmentioning
confidence: 99%
“…Therefore, it was suggested that an optimal combination of land and water exercises should be prescribed to patients with RA, dependent on the patients' needs and disease activity at that period of time. 57 Physical assessment and possible adverse effects of exercise…”
Section: Strengthening Exercisesmentioning
confidence: 99%
“…In human studies, we know that high-impact activities (e.g., gymnastics, jumping) produce a much higher gain in BMD [125][126][127][128][129][130][131][132] than lower-impact activities (e.g., swimming, cycling, walking) [133][134][135]. Weight training with high loads and low repetitions also results in more gain in BMD than training programs with low loads and high repetitions [136].…”
Section: Exercise To Improve and Maintain Bone Health Poststrokementioning
confidence: 99%
“…Research has also identified that marathon runners 15,16 have less BMD than Gymnasts and swimmers 17 have less BMD than runners. So, inspite of the active lifestyle, the form of physical activity we choose, decide the morphology and strength of bones of human skeleton.…”
Section: Discussionmentioning
confidence: 99%